PRODUCT EXHIBITION BERBASIS METAVERSE UNTUK PENJUALAN PERANGKAT MOBILE SELULER - Rifki Pebriansah Sulaeman (Journal of Informatics and Communication Technology (JICT), 2023)
The Metaverse is a technology very similar to the real world and can connect with others just like in the real world in various aspects such as economy, rules, social, and culture. The Metaverse has characteristics that are unique, immersive, connectivity, economic, arbitrary, and endless. The challenge faced is how to develop a Metaverse that suits the target users and replicates the Metaverse experience similar to the real world. The design thinking method includes empathizing with user personas, defining, ideating, prototyping with diagrams, and developing Metaverse interfaces, and testing using the Single Ease Question (SEQ) as a usability testing method with scores. It can help in the development of a Metaverse that facilitates visitors in terms of UI/UX and produces a Metaverse that is accepted by visitors to address issues in the design thinking stage through interviews with questionnaires in UI/UX. The average SEQ score obtained is 5. In conclusion, the Metaverse Product Exhibition Based on Metaverse for Mobile Device Sales is relatively easy to use. The findings in this research show that the development of the Metaverse Product Exhibition Based on Metaverse for Mobile Device Sales using the design thinking method can provide ease in smartphone store activities without leaving home with a Metaverse that closely resembles the real world within the Metaverse Product Exhibition Based on Metaverse for Mobile Device Sales.